Baseline Assessment of Marine Resources Caught by Fishermen in Selected Coastal Barangays of Cawayan, Masbate, Philippines - Ibañez, Jr. , Roger Y.; Velza, Jacob Frederick; Ompoc, Janice; Oporto, Mark Dave; Mobo, Froilan (Future Science / FSH-PH Publications, 2023)
Marine resources have been essential for human consumption and livelihood activities, particularly for small-scale fishermen in the fishing industry. This study employed a descriptive research design, utilizing interviews and structured survey questionnaires for data collection. The findings revealed the presence of 28 fish species caught by the fishermen in Cawayan, including Asian seabass, bisugo, dolphin fish, giant trevally, gold band goatfish, grouper, lattice monocle bream, mackerel tuna, mullet, needlefish, narrow barred, octopus, oxeye scad, pink shrimp, pin spotted spinefoot, pony fish, sardines, sailfish, shark, short mackerel, slip mouth fish, squid, stingray, threadfin emperor, whiting, and yellow stripe scad. The study also identified five shellfish species, namely baler shell, fierce shell, mother-of-pearl shell, scallop, and ark shell. Seaweed species, including sea moss and sea grapes, as well as the presence of blue crab, contributed to the diverse marine ecosystem. Age emerged as a significant factor in fishing, as older fishermen exhibited extensive knowledge and expertise in identifying the caught fish species. Younger individuals, on the other hand, demonstrated physical strength and minimized the risk of work-related injuries. Notably, a significant portion of fishermen (32%) operated boats they did not own, with motorboats being the preferred choice for the majority (93%). Additionally, 72% of respondents indicated that their fishing income covered only their daily expenses, while 57% lacked alternative sources of income during unfavorable weather conditions. The researchers recommend educating and equipping fishermen with the latest fishing knowledge and skills, facilitated by collaborative efforts among the Bureau of Fisheries and Aquatic Resources (BFAR), local government units (LGUs), community extensionists, and extension workers. Sharing sustainable and advanced fishing practices will contribute to the well-being and long-term prosperity of fishing communities.